Assessing the Prevalence of Dyslipidemia in Apparently Healthy Urban Obese Adults Residing in South Delhi, India - Kaur, Harmeet; Aeri, Bani Tamber (Jurnal Gizi dan Pangan, 2020)
The present research study was conducted to assess the prevalence and pattern of dyslipidemia in apparently healthy urban obese adults residing in South Delhi. Dyslipidemia and obesity are two prominent contributing risk factors for cardiovascular disease. This cross-sectional study was conducted among 150 apparently healthy obese adults with a body mass index of ≥25 kg/m2. Data regarding the socio-demographic characteristics as well as anthropometric parameters were collected. To evaluate serum lipid levels fasting blood samples were collected by trained technicians and analysis was carried out in a certified laboratory. Dyslipidemia was defined as the presence of hypercholesterolemia, high levels of low-density lipoprotein (LDL) cholesterol, and /or lower concentration of high-density lipoprotein (HDL), present alone or in combination. The overall prevalence of dyslipidemia was noted to be 78%. The prevalence was observed to be much higher in the obese female subjects (81.43%) than the obese males (75%). Mean triglycerides levels were significantly higher in the obese men than females while, HDL–C levels were higher in the female subjects (p<0.05). Further, it was seen that low concentration of HDL was the most prevailing deranged lipid parameter (52.67%) followed by elevated triglycerides levels (49.33%) and elevated LDL levels (39.33%) in these obese adults. The study thus highlights the importance of regular and timely screening for apparently healthy populations. Advocating suitable and timely medical and dietary interventions can help in both monitoring and avoiding further health-related complications.